Review of physical vapour deposition (PVD) techniques for hard coating - Mubarak, A.; Hamzah, Esah; Toff, M. R. M. (Faculty of Mechanical Engineering, 2005)
This paper is a review on the status of hard coating of various physical vapour deposition (PVD) techniques and compare their properties. The use of hard and wear resistant PVD coatings on cutting tools is now widespread in global manufacturing for reducing production cost and improving productivity, all of which are essential if industry is to remain economically competitive. The review includes the drawbacks of cathodic arc evaporation (CAE) and conventional magnetron sputtering processes and in this context their improvements. PVD techniques based on sputtering and cathodic arc methods are widely used to deposit hard coating for various cutting tools and many others. From the study, it was concluded that the CAE and radio frequency (RF) magnetron sputtering are the most widely used techniques and appropriate methods for thin film coating. Each technique has its own limitations and process parameters vary with the selection of PVD techniques. These techniques were further modified where uniform and dense coatings with improved adhesion can be achieved without the emission of macrodroplets from plasma streams